2016
DOI: 10.1002/apj.1964
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan microspheres modified with poly(ethylenimine) enhance the adsorption of methyl orange from aqueous solutions

Abstract: Chitosan (CS) microspheres were prepared by emulsion crosslinking, and the surfaces of the spheres were modified with poly(ethylenimine) (PEI) for preparing efficient adsorbents. Consequently, a series of PEI-modified CS (CS-PEI) microspheres with different ion exchange capacities (IECs) was prepared and used for the adsorption of methyl orange (MO). The adsorption performance of CS-PEI increased significantly with the increase of the sphere IECs, and the maximum adsorption capacity of 400.00 mg/g was achieved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Therefore, photocatalytic treatment of MO wastewater by blending chitosan and bentonite could be a feasible method. According to literature reports, 42,43 by modifying the material and introducing corresponding functional groups, the adsorption performance can be enhanced by increasing adsorption sites and chemical stability. Diethylenetriamine contains two primary amine groups and a secondary amine group in its molecules, which provided adsorption sites on the surface of the adsorbent by protonation under acidic conditions that favored electrostatic interaction towards negatively charged pollutants.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, photocatalytic treatment of MO wastewater by blending chitosan and bentonite could be a feasible method. According to literature reports, 42,43 by modifying the material and introducing corresponding functional groups, the adsorption performance can be enhanced by increasing adsorption sites and chemical stability. Diethylenetriamine contains two primary amine groups and a secondary amine group in its molecules, which provided adsorption sites on the surface of the adsorbent by protonation under acidic conditions that favored electrostatic interaction towards negatively charged pollutants.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the amine group is one of the most effective groups to remove contaminants from wastewater 25 . Thus, polyethylenimine (PEI), a cationic polyelectrolyte containing a large number of amino groups, exhibits strong adsorption ability for heavy metals through complexation or electrostatic interaction 26,27 . The graft of PEI on the surface of adsorbent can provide a large number of amino groups for the adsorption of heavy metals, thus improving the adsorption capacity of the adsorbent.…”
Section: Introductionmentioning
confidence: 99%
“…To improve the adsorption performance, it has been reported that adsorbent material was modified by high chelating coordination of S and N functional groups [18][19][20][21]. However, the reaction steps to achieve polyamine design were numerous in these reports.…”
Section: Introductionmentioning
confidence: 99%
“…Elwakeel [19] used glutaraldehyde and epichlorohydrine as a medium to bond triethylenetetramine with the chitosan chain through three reactions. Jing et al [20] prepared poly(ethylene imine) aminated chitosan derivatives with the aid of cross-linking agent glutaraldehyde by two reactions. In order to reduce the amount of solvents and reagents used in the multi-step experiment, in this work, aminated chitosan materials were prepared by simultaneous emulsion cross-linking of polyamine reagents.…”
Section: Introductionmentioning
confidence: 99%